Água e energia para a vida: o Movimento dos Atingidos por Barragens no Brasil (1991-2009) - Benincá, Dirceu (2010)
We live in a period of unprecedented environmental crisis. It results from a developmental option based on overexploitation of natural resources, the concentration of wealth and social exclusion. In this context, the demands for energy are becoming larger. Among the sources of energy, hydroelectricity occupies the largest share, which requires the gradual construction of dams. In all of its effects, we can count on severe impacts of social, ecological and symbolic order. In Brazil, there are few of medium and large rivers that have not been used on at least one point for the installation of hydroelectric facilities. According to the Movement of People Affected by Dams (MAB), the number of those who were expelled from their properties and living places because of those projects goes beyond one (1) million of Brazilians, of which about 70% of them have not their rights guaranteed. Thus, ultimately increasing the quota for the landless, jobless and without perspectives, increasing hunger, violence and misery. From the standpoint of symbolic and cultural aspects, it also exacerbates the consequences that occur as a result of these developments. This study takes a look at this scenario, trying to understand the logic behind the current energy model, so closely tied to capitalism, which is moved by profit at any cost. After examining the main impacts and conflicts generated by building dams - presented as a synonym for progress and development - it draws attention to the emergency of the submerged, that is, the regional organizations that led to the creation of the MAB (1991), with is now of national reach . The analysis of the subject is made against a background of two basic concepts, namely: sustainable development and ecological citizenship. The concepts and theoretical viewpoints, the multiple forms of resistance and complaints, the rights of those affected by dams, the achievements and proposals of the movement, its trajectory gives the structure of the other part of the approach. The objectives of the MAB and the fight are not restricted to seeking compensatory and remedial measures, but it turns to the construction of an energetic project, and ultimately to the establishment of a sustainable society, fair, solidary, democratic and respectful of the environment. For this dissertation, Water and Energy for Life, I used as a methodological resource, a participant observation, interviews with semi-structured scripts and the analysis of primary sources (documents, productions and the website of the movement). I have also made use of an extensive study of bibliography relative to the subject in consideration. I have started from the premise that the movement is an ideal place to build a political identity of those affected and to strengthen their citizenship, a situation which has proved largely true